A Design and Short-term Outcome Evaluation of the Commerce Faculty’s First Year Experience Mentoring Programme - Moeketsi, Themba (School of Management Studies, 2019)
This dissertation reports on a design and outcome evaluation of the Commerce First Year Experience (FYEM) programme. The FYEM programme is implemented by the Centre of Higher Education Department at the University of Cape Town. The FYEM programme is an academic and social supportive cooperation between universities faculties, departments, mentors and facilities for first year Commerce students. The collective efforts intend to: i) provide the first year students with a sense of belonging, ii) help students to adapt to university, and iii) offer academic and emotional to the students. A three repeated measure was used for this study. The measures were conducted in May, June and July. The first set of evaluation questions were based on the design of the programme: i) should mentoring be compulsory for first year students? ii) what is the effective duration for tertiary mentoring, iii) what is the most effective way of assigning mentors to mentees? and iv) what is the most effective medium for mentoring relationships? The second set of questions was based on the intended short-term outcomes of the programme: v) did the mentoring programme improve the psychosocial and academic attributes of students at observation time one to observation time two? vi) were these effects sustainable, meaning did the students continue to improve even after the end of the programme between observation time two and observation time three? and vii) was a difference between mentored and non-mentored students over time? The theory design results illustrated that selecting appropriate mentors requires setting up criteria based on certain characteristics. The duration of mentoring should be one year to allow the full transition of first-year students to the university. Another result showed that mentoring should be compulsory for the first year students provided that there is an opt-out option. Mentors and mentees should be given the opportunity to select their preferred individuals to work with and not be randomly assigned. Additionally, the most effective medium for mentoring was group sessions instead of one on one. The short-term outcome results for the mentoring programme were statistically insignificant due to the small sample size. There was, however, a small improvement in the means of the psychosocial and academic outcomes. After three months of the programme, there were no significant differences between the mentored and non-mentored students. The sample size may have contributed to the lack of effect as well as lack of qualitative data. In conclusion, it is evident that FYEM programme results were statistically insignificant. However, positive increases were observed for the mentored students’ sense of belonging, peer interaction, academic adjustment and engagement. The limitations of this study must be addressed so that more reliable and valid data can be gathered. The results from the design evaluation component can be used to improve the programmes’ implementation in 2017.